(untitled) (Interdisciplinary Studies Journal, 2021)
The Educating Cities movement began in 1990 in Barcelona and has since been used to develop governmental policies, such as the More Education Program in Brazil (COSTA; PAIVA, 2017). These educating cities are municipalities that engage their residents in activities encompassing individuals of all ages and in all spaces (BRASIL, 2011) and are currently present in 34 countries. For a municipality to become an educating city, certain requirements must be met, the first being registration with the Brazilian Network of Educating Cities (REBRACE). It is essential to undertake a historical review to uncover the city’s true identity, promoting knowledge exchange and learning through local experiences as a fundamental element for dissemination. Strategic actions must involve the collaboration of the entire community, not being an isolated initiative of the municipal government but a collective effort where everyone plays a vital role. This study aims to identify which Brazilian municipalities are considered educating cities. Data was obtained by consulting secondary information electronically available on the official REBRACE website. It was found that there are currently 21 certified educating cities in Brazil, namely: Horizonte (CE), Vitória (ES), Belo Horizonte (MG), Curitiba (PR), Camargo, Carazinho, Caxias do Sul, Marau, Nova Petrópolis, Porto Alegre, Santiago, São Gabriel, Soledade (RS), Guarulhos, Mauá, Santo André, Santos, São Bernardo do Campo, São Carlos, São Paulo, and Sorocaba (SP). Nationally, educating cities are predominantly located in the southern and southeastern regions of the country. However, in addition to identifying participating municipalities, it is essential to conduct further studies to investigate how municipal managers engage and implement this project in practice.